Triptolide induces toxicity in inner ear stem cells via promoting DNA damage. (December 2019) - Tang, Xuxia; Wang, Congpin; Hsieh, Yuelin; Wang, Chengjin; Wang, Jinyu; Han, Zhao; Cong, Ning; Ma, Rui; Chi, Fanglu
Abstract: Emerging evidence and clinical case reports have observed a risk of cytotoxic effects of triptolide in patients. We aimed to investigate the triptolide-induced toxicity in mouse inner ear stem cells. The utricular sensory epithelium from adult BALB/C6 mice was used for the isolation of inner ear stem cells. Sphere formation assay was applied to examine the stemness of the cells. Cell count kit-8 and Bromodeoxyuridine assays were employed to detect the cell proliferation ability. Cell apoptosis was measured with Annexin V-FITC & propidium iodide Apoptosis kit. The relative expression levels of gamma H2A histone family member X (γH2AX), tumor suppressor p53-binding protein 1 (53BP1) and optic atrophy 1 (OPA-1) were measured by Western Blot. Mitochondrial function was analyzed by the MitoGreen green-fluorescent mitochondrial dye kit. Triptolide significantly inhibited the cell viability and proliferation and suppressed the capability of sphere formation. Furthermore, triptolide induced apoptosis as indicated by increased expression of DNA damage repair markers γH2AX and 53BP1. Moreover, triptolide influenced the function of mitochondria by inducing the cleavage of OPA-1. Our work clarifies the toxicity of triptolide in mouse inner ear stem cells, which provides clues of the toxicology mechanism for future studies and basis for clinical use. Highlights: Triptolide significantly inhibits the cell viability and proliferation and suppresses the capability of sphere formation. Triptolide induces apoptosis as indicated by increased expression of DNA damage repair markers γH2AX and 53BP1. Triptolide influences the function of mitochondria by inducing the cleavage of OPA-1.